Introduction to simulation using SIMAN - Pegden, Claude Dennis; Shannon, Robert E., 1932-; Sadowski, Randall P (New York : McGraw-Hill, 1990)
This book provides a basic introduction to simulation and systems modelling using SIMAN - the fastest growing simulation language. The fundamental concepts of simulation modelling are presented along with methodologies used in applying simulation to business and engineering problems. Written by the creators of SIMAN, a commercial simulation software package, this book presents practical examples in the SIMAN language. More than just a user's manual, the book not only illustrates the practice of simulation in SIMAN but also offers a complete introduction to the
1. Introduction to modeling -- 2. Beginning the study -- 3. Basic modeling concepts -- 4. Model verification and validation -- 5. Interpreting simulation output -- 6. Station submodels and entity transfers -- 7. Animating the simulation by using cinema -- 8. Additional discrete modeling concepts -- 9. Advanced manufacturing features -- Interfacing user-written subprograms -- 11. Continuous and combined models -- 12. Variance reduction techniques.
includes bibliographical references and index
1
Keywords: SIMAN (Computer program language); Digital computer simulation